Optimization for Increasing Teacher Performance through Strengthening Teamwork, Interpersonal Communication, Adversity Intelligence, and Work Motivation (International Journal of Scientific Research and Management (IJSRM), 2023)
In educational institutions, teachers are a core part of the management element. Teacher Performance Assessment is an assessment of each item of the teacher’s main task activities in the context of career development, rank, and position. The implementation of a teacher’s main duties cannot be separated from a teacher’s ability to master knowledge, skills, and attitudes in carrying out their duties as a professional educator. To improve teacher performance, research is needed to obtain good information regarding other variables that can be used to improve teacher performance. This research aims to make efforts to improve teacher performance by researching the influence of teamwork, interpersonal communication, adversity quotient, and work motivation. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain optimal solutions to improve teacher performance. The population of this study was 289 PGRI Vocational School teachers in Bogor Regency. A sample was taken from this population using the Slovin formula and a sample of 168 people was obtained. The results of the analysis using the path analysis method show that there is a positive influence between teamwork and teacher performance with a large effect of βz1 = 0.254 so that strengthening teamwork can improve teacher performance. There is a positive influence between adversity quotient and teacher performance with a large effect of βz2 = 0.179 so that the strengthening of interpersonal communication can improve teacher performance. There is a positive influence between interpersonal communication and teacher performance with a large effect of βz3 = 0.183 so strengthening the adversity quotient can improve teacher performance. There is a positive influence between work motivation and teacher performance with a large effect of βz4 = 0.292 so strengthening work motivation can improve teacher performance. From the SITOREM analysis, the optimal solution is obtained, namely from the 27 indicators studied 14 indicators are in good condition so these indicators only need to be maintained or developed, and 13 indicators are still weak and need to be improved. Improvements to indicators that are still weak are complemented by a priority order for their handling. Good indicators are: 1) Ownership, 2) Resilience, 3) Achievement, 4) Job attachment, 5) Good supervision, 6) Adequate rewards, 7) Trust, 8) Harmony, 9) Completeness, 10) Empathy, 11) Openness, 12) Positivity, 13) Work Productivity and 14) Quantity of Work Results Indicators that need to be improved in order of priority for handling are as follows: 1st Control, 2nd Authenticity, 3rd Desire to get appreciation and recognition, 4 th Job Guarantee, 5 th Desire for power, 6 th Accountability, 7 th Group Goal Orientation, 8 th Coordination, 9 th Support, 10 th Equality, 11 th Quality of Work, 12 th Work Effectiveness, 13 th Work Efficiency.